Equity Valuation : United States Steel Corporation - Kyriakidis, Michail (2023)
This dissertation aims to determine the price target of United States Steel Corporation, a steel manufacturing company of historical significance which has recently experienced profitability issues. Despite previous issues the company finds itself in a transitionary environment towards sustainability, presenting a unique opportunity for the company to rebound from several years of financial mediocracy compared to its peers. In pursue of the fair value of U.S. Steel two model will be utilized, for the fundamental analysis a DCF model will be performed and for the relative valuation a Comparable Company Analysis (CCA) also known as a multiple’s valuation. Within the DCF three scenarios will be computed to depict the different economic environments that the company may undergo, with those being an optimistic, a recession and a base scenario. For each respective scenario, assumptions have been made which conform with the company strategy and macro-economic landscape. Following the research and assumptions considered the price target for U.S. Steel comes to $17.1 per share, categorized as a sell recommendation, due to the target being 20% lower than the trading price of $21.36 per share.